Characterization and Classification of Soils in Landslide Residual Zones to Estimate the Presence of Shallow Slip Plane - Noviyanto, Amir (UNIVERSITY OF LAMPUNG, 2025)
While landslide determination has traditionally relied on topography and geology, the connection between soil characteristics and landslide potential remains a relatively unexplored area. This study sets out to bridge this gap by investigating the relationship between soil properties and their classification and the likelihood of a shallow slip field triggering landslides. The research commenced with a survey of three landslide sites featuring diverse soil materials. Characterization and sampling were carried out on the residual zone left at the top of the landslide. The findings revealed that certain landslides could be identified as having potential slip planes only at a depth of 120 cm, while others could not. Two landslides in Magelang exhibited the presence of typical endopedon horizons, namely Bt (argillic). These argillic horizons serve as accumulation sites for fine and plastic clay materials. The low organic matter content also contributes to the instability and rapid dispersion of the structure. Meanwhile, the research also identified practical implications for landslide management. For instance, one of the landslides in Purworejo showed that the soil profile in the residual zone had low clay content and did not form a Bt horizon. However, the presence of shallow argillic with high clay content indicated a potential landslide risk. This finding suggests that landslides can be predicted based on soil characteristics, particularly the presence of argillic horizons. Moreover, the study identified specific soil types, such as Alfisols and Ultisols, as being prone to landslides. The Bt horizon, which can be protected by reducing erosion and runoff using silt pits, cover crops, and flow-breaking media, offers a practical solution for landslide prevention.